Empowering partnership: key lessons from the co-development of patient-oriented research with parents, researchers, and healthcare professionals - Wilson, Jacqueline M.; Kromm, Seija K.; Johns, Christine; Neraasen, Michelle L.; Chinhengo, Tapuwa; Anderson, Shannon D.; Fiedrich, Elsa; McNeil, Deborah (Frontiers in Health Services, 2025)
BackgroundCo-developing research in partnership with patients and families is integral to Learning Health Systems (LHSs). These partnerships advance LHS objectives by (1) ensuring innovation is relevant to local contexts, (2) accelerating evidence into practice, and (3) improving services and outcomes that are meaningful to patients and families. Despite the importance of patient and family engagement in LHSs, strategies that guide researchers to build and sustain teams of patients, clinicians, and other partners are under-reported.ObjectiveWe report actionable insights for co-developing research learned through our experience within Alberta's LHS.ContextParents from a provincial advisory group in Alberta identified the need to evaluate parents' experiences with family-centered care in Neonatal Intensive Care Units (NICUs). In response, a research team of parent partners, researchers, and clinicians is co-developing a validated experience measure for parents in NICUs.MethodsDuring co-development, the research team engaged in reflective practice through semi-structured discussion informed by Schön's Reflection Model. Notes from the discussion were thematically analyzed to identify insights and research co-development strategies.ResultsThree key insights and associated strategies were generated: (1) operationalizing co-development through a shared governance structure, terms of reference, and dedicated reflection; (2) adaptive approaches to team member involvement, renegotiating workflows, and addressing dissent; and (3) team evolution by nurturing reciprocity and utilizing existing partnerships to recruit members.ConclusionWe demonstrate how a team of patient partners, researchers, and clinicians can effectively co-develop research to address health system issues, and we present strategies to support patient-oriented research teams within LHSs.